2016
DOI: 10.1109/tec.2016.2540006
|View full text |Cite
|
Sign up to set email alerts
|

Field Validation of IEC 61400-27-1 Wind Generation Type 3 Model With Plant Power Factor Controller

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Generic WT models developed by IEC 61400-27-1 have been implemented, simulated and validated using field measurements in several scientific contributions, following the IEC validation procedure [8,9,12,13]. In [8], a Type 3 WT developed by standard IEC 61400-27-1 was validated using the measurements of a real WT following the IEC guidelines.…”
Section: Spanish Grid Code and Procedures For Verification Validationmentioning
confidence: 99%
“…Generic WT models developed by IEC 61400-27-1 have been implemented, simulated and validated using field measurements in several scientific contributions, following the IEC validation procedure [8,9,12,13]. In [8], a Type 3 WT developed by standard IEC 61400-27-1 was validated using the measurements of a real WT following the IEC guidelines.…”
Section: Spanish Grid Code and Procedures For Verification Validationmentioning
confidence: 99%
“…Since the grid model is not considered in the playback approach, additional uncertainties are not included, and the differences between simulation results are thus reduced. In this sense, these two simulation methodologies are compared under a power factor change event in [22], where it is observed that the full grid simulation approach is able to capture only the non-oscillatory behavior, while the playback approach can capture the impact of the oscillatory grid voltage. Therefore, the playback validation method is recommended by IEC guidelines for assessing the model accuracy [34], and it will be followed in the present work for validation purposes.…”
Section: Need For the Validation Of Generic Wind Turbine Modelsmentioning
confidence: 99%
“…Finally, Reference [20] also performs validation tasks during faults, although they compare a WT model with an analytical method. Therefore, in view of the above, Reference [21] is the only work addressing the performance of generic Type 3 WT models using DIgSILENT-PowerFactory. However, although PF is the tool used, the responses at plant level during changes on the reference points are analyzed, so that no voltage dip tests at a WT model level are conducted.…”
Section: Introductionmentioning
confidence: 99%